Efficacy of Contezolid in the Treatment of Catheter-Related Bloodstream Infections Caused by Methicillin-Resistant Staphylococcus aureus in a Patient with Hepatorenal Syndrome and Acute Kidney Injury: A Case Report - Zhang X; Huang H; Wang J; Wei B (Infection and Drug Resistance)
Xiucui Zhang,* Huili Huang,* Jianrong Wang, Bo Wei Department of Infectious Disease, Changzheng Hospital, Navy Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Wei, Department of infectious disease, Changzheng Hospital, Navy Medical University, Shanghai, People’s Republic of China, Email weibi0816@163.comAbstract: The Hepatorenal Syndrome-Acute Kidney Injury (HRS-AKI) patients infected with methicillin-resistant Staphylococcus aureus (MRSA) urgently require safe and effective treatment options due to their compromised hepatic and renal functions, as well as thrombocytopenia resulting from hypersplenism. In our case, an HRS-AKI patient who underwent continuous renal replacement therapy for fluid overload developed fever with chills. His blood tests indicated elevated C-reactive protein and neutrophils, low platelet count, and bilateral lung infiltrates. Subsequently, his blood culture and catheter culture confirmed a catheter-related MRSA bloodstream infection. To address this complex clinical challenge, a novel oxazolidinone antibiotic, contezolid (800mg orally every 12 hours), was introduced into the patient’s anti-infection regimen. Notably, the patient exhibited remarkable improvements and responded favorably to this treatment. During subsequent follow-up, no recurrence of the infection or drug-related adverse events was observed. The successful utilization of contezolid in this case underscores its potential as a novel therapeutic option for treating MRSA infections in patients with HRS-AKI.Keywords: Hepatorenal syndrome-acute kidney injury, methicillin-resistant Staphylococcus aureus, bloodstream infection, contezolid